Modersmyb - moderskap - mãnskoskap. - Konsthallen Göteborg (Göteborg : Konsthalle Göteborg, 1979)
Andréen, Barbro ; Berggren, Eva ; Bergmann, Benedicte ; Beskow, Synnöve ; Cronqvist, Lena ; Englund, Monica ; Hammarsten-Mc Faul, Ulla ; Helander, Joanna ; etc.
Modersmyb - moderskap - mãnskoskap, Konsthalle Göteborg, 29 sept - 25 nov 1979
boek